Contribution of Modern Movement to the Construction of a New Urban Profile for Residential Architecture in Lima from 1945 to 1965 - Campos-García-Calderón, Inés Magdalena (Universidad de Lima. Carrera de Arquitectura, 2017)
Modern Movement in Peru is comprised between 1945 and 1965. At that time, the Peruvian architects who studied abroad returned to the country as well as the foreigners who arrived toPeru and carried out their profession heavily influenced by the new architecture of the twentieth century — a result from European vanguards such as Bauhaus and De Stijl —, by movements emerged in other countries, by the International Congresses of Modern Architecture (CIAM), and by those who developed their own architecture. The Modern Movement promoted an important contribution to Lima architecture. By selecting symbolic cases, this article tries to identify the wayelements in the facades designed by the modern architects of Peru contributed to the construction of a new urban profile in Lima residential architecture.